Diet supplementation with flaxseed stimulates gut metabolism in mice - Sopková , Drahomira; Vlčková , Radoslava; Andrejčáková , Zuzana; Gancarčíková , Soňa (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
Essential polyunsaturated fatty acids (PUFAs) in the feed may affect the gastrointestinal microbiota. The present study investigated the effect of 35-day supplementation of mice diet with 5% concentration of high-ω-3 PUFAs in flaxseed with focus on intestinal metabolism of mice. Capillary isotachophoresis method was used for the assessment of the level of organic acids in the gut material and faeces. Supplementation of flaxseed increased the level of organic acids in the caecum (acetic, propionic, butyric and valeric acids) and faeces (lactic, acetic, butyric acids). The most significant effect was observed on day 28 of flaxseed supplementation. The investigated additive had a stimulatory effect on intestinal metabolism and fermentation activity of beneficial bacteria.